2016
DOI: 10.1242/dev.138776
|View full text |Cite
|
Sign up to set email alerts
|

Conditional mutation of Smc5 in mouse embryonic stem cells perturbs condensin localization and mitotic progression

Abstract: Correct duplication of stem cell genetic material and its appropriate segregation into daughter cells are requisites for tissue, organ and organism homeostasis. Disruption of stem cell genomic integrity can lead to developmental abnormalities and cancer. Roles of the Smc5/6 structural maintenance of chromosomes complex in pluripotent stem cell genome maintenance have not been investigated, despite its important roles in DNA synthesis, DNA repair and chromosome segregation as evaluated in other model systems. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…Therefore, it was hypothesized that mutation of Smc5 would affect TOP2A localization in mouse oocytes. However, no defects in TOP2A localization were observed, which corresponds to what has been reported for Smc5 cKO in mouse embryonic stem cells (Pryzhkova and Jordan, 2016). Studies of yeast SMC5/6 have shown that the complex is linked with TopoIIdependent catenation/decatenation functions (Jeppsson et al, 2014;Kanno et al, 2015;Kegel et al, 2011).…”
Section: Smc5 Is a Maternal-effect Genesupporting
confidence: 82%
See 3 more Smart Citations
“…Therefore, it was hypothesized that mutation of Smc5 would affect TOP2A localization in mouse oocytes. However, no defects in TOP2A localization were observed, which corresponds to what has been reported for Smc5 cKO in mouse embryonic stem cells (Pryzhkova and Jordan, 2016). Studies of yeast SMC5/6 have shown that the complex is linked with TopoIIdependent catenation/decatenation functions (Jeppsson et al, 2014;Kanno et al, 2015;Kegel et al, 2011).…”
Section: Smc5 Is a Maternal-effect Genesupporting
confidence: 82%
“…S5). This phenotype is reminiscent of the mitotic catastrophe observed in Smc5 cKO mouse embryonic stem cells (Pryzhkova and Jordan, 2016). Fig.…”
Section: Smc5/6 Localization Pattern Implicates Multiple Functions Dumentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, the impaired adipogenesis was revealed to be caused by G2/M phase arrest during the process of MCE. Accordingly, in mouse embryonic stem cells with a conditional KO of Smc5, Pryzhkova et al 47 found that the downregulation of Smc5 results in cells accumulating in the G2 phase. Moreover, mitotic defects are apparent only when the function of SMC5/6 is compromised during the S/G2 phases, suggesting its crucial role in the sister chromatid disjunction.…”
Section: Discussionmentioning
confidence: 99%